Rockery potential chasmophytes in Velliangiri hills of South-Western Ghats of Tamil Nadu - Thomas, Binu; Rajendran, A. (Indian Journal of Horticulture, 2013)
The present paper highlights the 34 ornamental chasmophytic species belonging to 20 families collected from the rock crevices of Veliangiri Hills of Southern Western Ghats of Tamil Nadu, India. Most of the ornamental chasmophytes are herbacelous which probably are the results of the harsh geographical environment in the study area. In this harsh environment chasmophytic plants develop adaptive physiological and ecological characteristics, developing into cushion plants, herbs with an attractive shape and size in cracks and fissures of rock face. Their flowers are very bright and showy and possess certain biological peculiarities of different interesting adaptations and flower colour which can attract many people have been identified for possible cultivation in rock garden for ornamental purposes and psychological beneficial.